2019
DOI: 10.1093/ecco-jcc/jjz185
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Emergency Admissions With Ulcerative Colitis Between 2007 and 2017 in England

Abstract: Abstract Background and Aims Patients with ulcerative colitis [UC] may present as emergencies and require rapid escalation of therapy. This study aimed to assess the mortality, colectomy, and readmission risks, during and following a first emergency admission with UC. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
25
1
1
Order By: Relevance
“…31,34 Although randomised controlled trials (RCTs) do not suggest any difference in efficacy and safety between infliximab and cyclosporine as rescue therapies for steroid-refractory ASUC, 11,12 observational data suggest a lower risk of long-term colectomy with infliximab compared with cyclosporine. 3 This may be one of the reasons why infliximab is preferred over cyclosporine as rescue therapy but the experience of treating physicians and patient preferences, should also be taken into account. A theoretical advantage of infliximab over cyclosporine is that it is an easier treatment regimen with less monitoring and this may explain why many gastroenterologists are more familiar with infliximab than with cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,34 Although randomised controlled trials (RCTs) do not suggest any difference in efficacy and safety between infliximab and cyclosporine as rescue therapies for steroid-refractory ASUC, 11,12 observational data suggest a lower risk of long-term colectomy with infliximab compared with cyclosporine. 3 This may be one of the reasons why infliximab is preferred over cyclosporine as rescue therapy but the experience of treating physicians and patient preferences, should also be taken into account. A theoretical advantage of infliximab over cyclosporine is that it is an easier treatment regimen with less monitoring and this may explain why many gastroenterologists are more familiar with infliximab than with cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although acute severe ulcerative colitis (ASUC) is a potentially life-threatening condition, its mortality rate has dropped dramatically over the past decades to approximately 1%. [3][4][5] This improved outcome is attributed to the introduction of intensive intravenous treatment (IIVT) with steroids and a policy of early surgery for non-responders. However, despite the use of steroids, at least 30% of patients fail to respond and, until recently, were candidates for colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The 2018 publication from Pollok's group, investigating nationwide temporal trends in medical and surgical admissions for IBD between 2003 and 2013, also suggests reducing elective surgery rates with non‐significant reductions in emergency surgery 17 . King et al, also using HES data, demonstrated a reduction in colectomies up to one year after emergency admission for UC between 2007 and 2017, but they do not state results beyond 29 . Bodger's group demonstrate widespread improvements in emergency UC admissions, including improvement in colectomy free discharge after emergency UC admissions during a similar time period to this study, but again focus on the emergency admission and early readmissions rather than longer term follow‐up 18 .…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant reduction in risk of further surgery for females. The phenomenon that males have been shown to be at increased risk of major abdominal surgery in CD has, however, been previously observed, 40 and we have previously shown a protective association of female sex in those with acute ulcerative colitis in relation to surgical intervention 41 . It may be that this study was underpowered to demonstrate a significant difference in the sexes.…”
Section: Discussionmentioning
confidence: 55%